2020
DOI: 10.1177/1082013220980204
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and enterotoxin gene profiles of Staphylococcus aureus isolated from retail chicken meat

Abstract: The present study was conducted to evaluate the prevalence and enterotoxin gene profiles of Staphylococcus aureus isolated from 120 chicken meat marketed in retail outlets of Chennai, India. It was observed that total of 120 meat samples collected from different retail outlets, 66.67% (80/120) of the samples were positive for the presence of S. aureus based on biochemical characterization and species specific PCR based on thermonuclease gene ( nuc). Enterotoxin gene profiling of the isolates for 9 genes ( sea-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
2
5
4
Order By: Relevance
“…In addition, Kim et al [26] reported that out of 200 chicken meat samples collected in South Korea, 94 were found to be positive (47%) for S. aureus. This number was lower compared to the value reported in Savariraj et al [20], where around 66.67% of samples obtained from in retail outlets in Chennai, India, resulted positive for S. aureus.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…In addition, Kim et al [26] reported that out of 200 chicken meat samples collected in South Korea, 94 were found to be positive (47%) for S. aureus. This number was lower compared to the value reported in Savariraj et al [20], where around 66.67% of samples obtained from in retail outlets in Chennai, India, resulted positive for S. aureus.…”
Section: Discussioncontrasting
confidence: 74%
“…The sample volume was then inoculated into Mannitol Salt Agar (MSA) (Merck 1.05404.0500) and was incubated at 35°C for 24 h. Yellow colonies growing on the MSA were described as positive S. aureus, while red colonies represented other species of Staphylococcus [19]. The suspected colonies were identified by mannitol fermentation, Gram staining, a catalase test, and a coagulase test as per standard protocol [20]. Gram staining was conducted aseptically on the identified colonies.…”
Section: Isolation and Identification Of S Aureusmentioning
confidence: 99%
“…The chain of distribution of the enterotoxin genes from our study was seg>sej>sea>sep>sec>seb>sed>see,she,ser> sei>sek,sel. This was different from those from other studies, such as seb>seg>sei>sec>sed>sej (Savariraj et al, 2020). Kitai et al (2005) reported the distribution of seb>sea>sec>sed.…”
Section: Discussioncontrasting
confidence: 86%
“…Most MRSA isolates by Wu et al (2019) were MDR and harbored ≥1 SE gene, similar to our findings. Lower profiling of SEs (13 -83%) has been documented (Kitai et al, 2005;Li et al, 2018;Savariraj et al, 2020;Tegegne et al, 2021) compared to those of our study. The chain of distribution of the enterotoxin genes from our study was seg>sej>sea>sep>sec>seb>sed>see,she,ser> sei>sek,sel.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation